Estudo da atratividade dos ambientes de comunidades virtuais: Análise Comparativa LinkedIn e Orkut - Koo, Lawrence Chung (2006)
The reality of digital world is closely related to our daily life in such a way that the cyber culture footsteps are marked digitally in all the aspects of our life. These facts can also be applied to our relationships, transforming physical contact into virtual hypermidiatic connections. A large quantity of virtual community is added to cyber space each day, however, significant part of them lose their attractiveness soon after they are launched to the market. We would like to understand the reasons why the failure of these sites happen, and list the main factors which have to be considered in the design phase. The semiotic qualitative analysis performed in this research work has the objective to demonstrate how the attractiveness and communicability of the relationship site such as Orkut and LinkedIn is one of the key factors to drive the successful construction of virtual networks and create loyalty to the users. The methodology that we will apply to this research work is based in the General Theory of Signs from Charles Peirce. We chose the Orkut and LinkedIn relationship sites as study objects